The Effectiveness of Augmented Reality-based Arthropod Book in terms of Student's Biology Learning Outcomes - Maryana; Meyninda Destiara; Nurul Himmah (Indonesian Journal of Mathematics and Natural Science Education, 2022)
Abstract Learning media has a very important function in the learning process. The large number of students who lack interest in learning is influenced by the lack of use of teaching media by teachers, so that students are getting bored with the use of media that is less varied. Based on this view, this study focused on examining the effectiveness of augmented reality-based arthropod book in terms of students’ biology learning outcomes. This study aims to determine the biology learning outcomes of students using augmented reality-based Arthropoda book, as well as to determine the effectiveness of the book. This type of research is a field research, in which a research that goes directly to the field. In addition, data were obtained in quantitative methods with the type of pre-experimental design and the One Group Pretest-Posttest design. The results of this study indicate that biology learning process using augmented reality-based Arthropoda book is more effective, which can be seen from the learning outcomes of students increased however the difference is not significant, because the N-Gain Score for pretest and posttest scores reached in the moderate or quite effective category.